South China Sea energy and security conflicts - Daniels, Christopher L. 1982- (Global flashpoints, 2014)
In [this book], foreign policy analyst Christopher L. Daniels analyzes the core causes of the dispute over territorial claims in the South China Sea, which separates some of the world's fastest-growing economies. Starting with the question of access to the billions of barrels of oil and trillions of cubic feet of natural gas presently thought to lie beneath the region's territorial waters and islands, Daniels considers the race for resources and military dominancy along with the rapidly increasing domestic demand for electricity and industrial output of the regional players. [This book] takes on such troubling questions as the impact of this conflict on global oil and gas prices; China's growth both economically and as a regional military hegemon; and the recent, often rocky, international efforts to mediate the conflict. In addition to policy recommendations for peaceful resolutions to this emerging international challenge, the book includes maps, graphs, primary sources, and overviews of key players-individual and institutional-in what may well be the next great conflict in East Asia.